Quality of life in patients with achalasia: Associations with Eckardt score and objective treatment outcomes after peroral endoscopic myotomy - Evensen, Helge; Hjermstad, Marianne Jensen; Cvancarova, Milada; Kristensen, Vendel; Larssen, Lene; Skattum, Jorunn; Hauge, Truls; Sandstad, Olav; Medhus, Asle W. (Endoscopy International Open, 2022)
Background and study aims Knowledge on self-reported quality of life (QoL) in achalasia and QoL improvements after peroral endoscopic myotomy (POEM) is limited. Furthermore, the clinical role of QoL in achalasia follow-up has not been evaluated. The present study aimed to examine QoL in achalasia patients before and after POEM and assess associations between QoL, Eckardt score (ES) and objective results.Patients and methods This was a single-center prospective study of treatment-naïve achalasia patients with 12-month follow-up after POEM including manometry, upper endoscopy, 24-hour pH registration, and timed barium esophagogram. QoL data were registered using European Organisation for Research and Treatment of Cancer core questionnaire (QLQ-C30) and esophageal module (QLQ-OES18). Comparison with a reference population was performed to assess impact of achalasia on QoL and effect of therapy. Mixed models for repeated measures were applied.Results Fifty patients (26 females) with a median age of 47 years (18–76) were included. Before treatment, all QoL domains were significantly impaired compared with an age- and gender-adjusted reference population (P < 0.05). No significant QoL-differences were found after POEM, except for fatigue and nausea/vomiting. Clinically relevant QoL improvement was observed in ≥ 50 % of the patients in all QoL domains, except for physical and role functioning. QoL was significantly associated with ES (P < 0.05) but not with objective results.Conclusions Achalasia is associated with severe QoL impairment. Following POEM, a significant and clinically relevant QoL improvement is observed. QoL is associated with ES, but not with objective results after POEM.